2012
DOI: 10.1103/physreve.86.045202
|View full text |Cite
|
Sign up to set email alerts
|

Two- and three-dimensional standing waves in a reaction-diffusion system

Abstract: We observe standing waves of chemical concentration in thin layers [quasi-two-dimensional (2D)] and capillaries [three-dimensional (3D)] containing the aqueous Belousov-Zhabotinsky reaction in a reverse microemulsion stabilized by the ionic surfactant sodium bis-2-ethylhexyl sulfosuccinate (AOT) and with cyclo-octane as the continuous phase. The 3D structures are oscillatory lamellae or square-packed cylinders at high and low volume fractions, respectively, of aqueous droplets. These patterns correspond to osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In our experiments, the BZ‐AOT experimental medium is a far‐from‐equilibrium dynamical system within a batch reactor, and so over time the system must approach and ultimately reach equilibrium. Previous experiments in the BZ‐AOT system have shown that standing waves can transition to traveling waves ,. The wavelength of the pattern was halved in the transition observed by Kaminaga et al ., and transitions to spirals and packet waves were reported by Bánsági et al .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In our experiments, the BZ‐AOT experimental medium is a far‐from‐equilibrium dynamical system within a batch reactor, and so over time the system must approach and ultimately reach equilibrium. Previous experiments in the BZ‐AOT system have shown that standing waves can transition to traveling waves ,. The wavelength of the pattern was halved in the transition observed by Kaminaga et al ., and transitions to spirals and packet waves were reported by Bánsági et al .…”
Section: Resultsmentioning
confidence: 80%
“…Turing patterns, bulk oscillations and waves have been observed in the Belousov‐Zhabotinsky (BZ) reaction incorporated into an AOT (dioctyl sodium sulfosuccinate) reverse microemulsion. Multiple types of waves have been observed in this system, including standing waves ,. Localized domains of standing waves have also been reported .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…We have utilized tomographic techniques to study three-dimensional Turing patterns and 3D standing waves in the BZ-AOT system. 32,33 Examples of such 3D patterns are shown in Figs. 3 and 4.…”
Section: The Bz-aot Systemmentioning
confidence: 98%
“…They are, e.g., often composed of several coupled nonlinear equations and/ or include higher order nonlinearities (see e.g. [3,21,22,[44][45][46][47][48][49]). Moreover, traveling waves can occur far from the onset of pattern formation.…”
Section: Reflection-induced Standing Waves In Models For a Chemical Rmentioning
confidence: 99%